Keputusan Rodrigo Duterte Menarik Filipina Keluar dari Keanggotaan International Criminal Court (ICC) 2018 - Suseno, Parsit (University of Jember, 2021)
The anti-narcotics policy during the reign of Rodrigo Duterte was intended to eradicate narcotics in the Philippines. The Philippines according to the rules of the Rome Statute are required to cooperate in the ICC investigation regarding indications of crimes against humanity in the implementation of policies. On the other hand, Rodrigo Duterte ordered local security forces not to cooperate with all forms of investigations carried out by the ICC in the Philippines. As of March 14, 2018 President Rodrigo Duterte said that the Philippines would revoke the ratification of the Rome Statute and leave the ICC membership. This study aims to analyze the reasons underlying the Duterte Decision through Graham T. Allison rational actor model theory. Based on the theory of the rational actor model, there are some policy alternatives to decide to get optimal result. Based on these, the decision to withdrawing Philippines membership from ICC is an effort to continue the implementation of anti-narcotics policies as Philipinnes national interest without ICC intervention.